2013
DOI: 10.1007/s00415-013-6846-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnostic yield of lumbar puncture in investigation of suspected subarachnoid haemorrhage: a retrospective study

Abstract: The diagnostic algorithm of computerized tomography (CT) and lumbar puncture (LP) for suspected subarachnoid haemorrhage (SAH) has lately been challenged by the advancement of radiological techniques, such as higher resolution offered by newer generation CT-scanners and increased availability of CT-angiography. A purely radiological workup of suspected SAH offers great advantages for both patients and the health care system, but the risks of abandoning LP in this setting are not well investigated. We have char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Six studies examined diagnostic accuracy of xanthrochromia on CSF analysis, but investigators used variable methods to assess xanthochromia ranging from visible inspection to multiple different spectrophotometric assays (Table , Figure ) . For visible xanthochromia the pooled meta‐analysis results were as follows: sensitivity was 85% (95% CI = 66% to 96%, I 2 = 0%), specificity as 97% (95% CI = 96% to 98%, I 2 = 13%), LR+ was 24.67 (95% CI = 12.13 to 50.14, I 2 = 64%), and LR− was 0.22 (95% CI = 0.09 to 0.54, I 2 = 13%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies examined diagnostic accuracy of xanthrochromia on CSF analysis, but investigators used variable methods to assess xanthochromia ranging from visible inspection to multiple different spectrophotometric assays (Table , Figure ) . For visible xanthochromia the pooled meta‐analysis results were as follows: sensitivity was 85% (95% CI = 66% to 96%, I 2 = 0%), specificity as 97% (95% CI = 96% to 98%, I 2 = 13%), LR+ was 24.67 (95% CI = 12.13 to 50.14, I 2 = 64%), and LR− was 0.22 (95% CI = 0.09 to 0.54, I 2 = 13%).…”
Section: Resultsmentioning
confidence: 99%
“…Brunell et al noted that LP provided an alternative diagnosis in 3% of suspected SAH cases, but only altered subsequent management in 0.44% of individuals who had an LP. This equates to 227 LPs (1/0.0044) to identify one central nervous system infection requiring antibiotics in suspected SAH patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the low rates of patients receiving lumbar puncture and catheter angiography in our study, the possibility of missed SAH may not be excluded. Nevertheless, based on the high sensitivity of the modern CT to detect SAH and CTA/MRA to detect aneurysm and the fact that no patients developed SAH during at least 6 months of follow-up, the contribution of missed SAH to the low SAH percentage in our study may be minor [17,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Brunell and colleagues found that a LP could reveal an alternative diagnosis in 3% of the patients, eg, meningitis. 19 Post-dural-puncture headache occurs in many, and patients with pre-morbid headaches are particularly at risk. 20 Rare serious complications include cerebral venous sinus thrombosis, CNS infections, and brain herniation.…”
Section: Post Contrast T1-weighted Mri (Picture In the Middle) Shows mentioning
confidence: 99%